Nitrogen-doped mesoporous activated carbon from Lentinus edodes residue: an optimized adsorbent for pharmaceuticals in aqueous solutions - Chu, Bei; Lou, Yichen; Tan, Yixin; Lin, Jiawei; Liu, Xingcheng (Frontiers in Chemistry, 2024)
In this study, phosphoric acid activation was employed to synthesize nitrogen-doped mesoporous activated carbon (designated as MR1) from Lentinus edodes (shiitake mushroom) residue, while aiming to efficiently remove acetaminophen (APAP), carbamazepine (CBZ), and metronidazole (MNZ) from aqueous solutions. We characterized the physicochemical properties of the produced adsorbents using scanning electron microscopy (SEM), nitrogen adsorption isotherms, and X-ray photoelectron spectroscopy (XPS). MR1, MR2, and MR3 were prepared using phosphoric acid impregnation ratios of 1, 2, and 3 mL/g, respectively. Notably, MR1 exhibited a significant mesoporous structure with a volume of 0.825 cm3/g and a quaternary nitrogen content of 2.6%. This endowed MR1 with a high adsorption capacity for APAP, CBZ, and MNZ, positioning it as a promising candidate for water purification applications. The adsorption behavior of the contaminants followed the Freundlich isotherm model, suggesting a multilayer adsorption process. Notably, MR1 showed excellent durability and recyclability, maintaining 95% of its initial adsorption efficiency after five regeneration cycles and indicating its potential for sustainable use in water treatment processes.